Immunomodulation by Gut Microbiota: Role of Toll-Like Receptor Expressed by T Cells. (24th July 2014) - Valentini, Mariagrazia; Piermattei, Alessia; Di Sante, Gabriele; Migliara, Giuseppe; Delogu, Giovanni; Ria, Francesco
Abstract : A close relationship exists between gut microbiota and immune responses. An imbalance of this relationship can determine local and systemic immune diseases. In fact the immune system plays an essential role in maintaining the homeostasis with the microbiota that normally resides in the gut, while, at the same time, the gut microbiota influences the immune system, modulating number and function of effector and regulatory T cells. To achieve this aim, mutual regulation between immune system and microbiota is achieved through several mechanisms, including the engagement of toll-like receptors (TLRs), pathogen-specific receptors expressed on numerous cell types. TLRs are able to recognize ligands from commensal or pathogen microbiota to maintain the tolerance or trigger the immune response. In this review, we summarize the latest evidences about the role of TLRs expressed in adaptive T cells, to understand how the immune system promotes intestinal homeostasis, fights invasion by pathogens, and is modulated by the intestinal microbiota.